Development of Phet Simulation-Based Mathematics Logic E-Modules in Increasing Students' Mathematical Reasoning Ability - Oktaviana, Dwi; Susiaty, Utin Desy; Firdaus, Muhamad; Prihatin, Iwit (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2023)
This research is represented through digital teaching with online learning simulations used by SMK teachers in learning mathematical logic that has not improved students' mathematical reasoning abilities. This study aims to describe the feasibility, attractiveness, and effectiveness of the PhET simulation-based mathematical logic e-module in improving students' mathematical reasoning abilities. This research method is the R and D. The research subjects were students of SMK Koperasi Pontianak majoring in Multimedia. Research data were collected using indirect communication techniques and measurements with data collection tools in the form of expert validation sheets, student and teacher response questionnaires, and test questions. Based on the results, it can be concluded that the e-module of mathematical logic with PhET simulation at the valid criterion, very interesting and effective. The results of this study can be implemented in the process of learning mathematical logic digitally through PhET simulation learning to improve students' mathematical reasoning abilities.Penelitian ini direpresentasikan melalui bahan ajar digital dengan simulasi pembelajaran online yang digunakan oleh guru SMK dalam pembelajaran logika matematika belum meningkatkan kemampuan penalaran matematis siswa. Penelitian ini bertujuan untuk mendeskripsikan kelayakan, kemenarikan dan keefektifan dari e-modul logika matematika berbasis PhET simulation dalam meningkatkan kemampuan penalaran matematis siswa. Metode penelitian ini adalah metode R and D. Subjek penelitian adalah siswa SMK Koperasi Pontianak tepatnya jurusan Multimedia. Data penelitian dikumpulkan menggunakan teknik komunikasi tidak langsung dan pengukuran dengan alat pengumpul data berupa lembar validasi ahli, angket respon siswa dan guru serta soal tes. Berdasarkan hasil penelitian dan pembahasan, dapat disimpulkan bahwa e-modul logika matematika dengan PhET simulation pada tingkat kriteria valid, sangat menarik dan efektif untuk menyelesaikan kesulitan pada siswa khususnya pada materi logika matematika. Hasil penelitian ini dapat diimplementasikan pada proses pembelajaran logika matematika secara digital serta melalui simulasi pembelajaran PhET simulation untuk lebih meningkatkan kemampuan penalaran matematis siswa.